Thermal study in solid state of Zn(II)-diclofenac complex: Behavior kinetic of dehydration, transition phase and thermal decomposition - Kobelnik, Marcelo [UNESP]; Quarcioni, Valdecir Ângelo; Ribeiro, Clovis Augusto [UNESP]; Capela, Jorge Manuel Vieira [UNESP]; Dias, Diogines dos Santos [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Wiley, 2010)
The dehydration, thermal decomposition and transition phase stage of Zn(II)-diclofenac compoundwere studied by simultaneous TG-DTA and DSC techniques. The TG and DSC curves of this compoundwere obtained with the mass of sample of 2 and 5 mg. Additionally, DSC curves were carried out inopened and closed a-alumina pans under static and nitrogen atmosphere. The DTA and DSC curves showthat this compound possesses exothermic transition phase between 170-180 ºC, which it is irreversible(monotropic reaction). The kinetics study of this transition phase stage was evaluated by DSC undernon-isothermal conditions. The obtained data were evaluated with the isoconversional method, where thevalues of activation energy (Ea/kJmol-1) was plotted in function of the conversion degree (a). The resultsshow that due to mass sample, different activation energies were obtained. From these curves a tendencycan be seen where the plots maintain the same profile for closed lids and almost run parallel to each other.
Keywords: Zn(II)-diclofenac complex; Thermal behavior; Transition phase; Kinetic